PENGARUH MEDIA GAMBAR TERHADAP MINAT BELAJAR ANAK USIA DINI DI PAUD IMANUEL OEMORO - Paulina Taneo, Heppi; Yohana Yuniati; Ambara S Mardani; Credo G Betty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning interest in early childhood is one of the key factors determining the success of the learning process in early childhood education (PAUD). Low learning interest is often caused by the use of boring and unattractive learning media, as found at PAUD Imanuel Oemoro, where children tended to be less enthusiastic, easily bored, and lacked focus during learning. This study aims to determine the effect of picture media on the learning interest of early childhood children at PAUD Imanuel Oemoro. This study used a quantitative approach with a pre-experimental one-group pretest-posttest design. The research sample consisted of 15 children aged 4-6 years selected through purposive sampling. Data were collected using an observation checklist and analyzed using the Wilcoxon test since the data were not normally distributed. The results showed a significance value of 0.001 (< 0.05), meaning Ha was accepted, indicating a significant effect of using picture media on children's learning interest. Children's learning interest scores increased from a range of 17-25 before treatment to 27-35 after treatment. Children became more enthusiastic, actively asked questions, engaged in discussion, and stayed focused during learning activities after picture media was implemented. This study concludes that picture media is effective as a learning medium to increase early childhood learning interesKeywords : picture media; learning interest; early childhood